THE INFLUENCE OF FOOTBALL IN SOME THYROID FUNCTIONS AND THE LEVEL OF A NUMBER OF BLOOD AND BIOCHEMICAL PARAMETERS OF A GROUP OF PLAYERS - Ruaa Hussein Alwan (Proximus Journal Publishing, 2024)
This research was designed to study the change in the concentrations of thyroid hormones and a number of blood measures during physical training of football players, who number (40) samples, and their ages range between (20-40) years. Samples are divided into weight categories depending on the values of body mass index (BMI). They were also divided into two categories, the first group (20-29) years and the second group (30-39) years. The results of the study showed the high concentration of thyroxine (T4) significantly (P <0.05) after the match or physical training compared to the results before the match, while did not appear a significant change in (T3) concentration after the game compared to the results before the game, the blood tests indicated good levels in the amount of hemoglobin among players compared to natural proportions. It is concluded from this study that the hormone (T4) changes its concentration after conducting physical training>
Keywords: training; football